The Relationship Between Avoidant Attachment and Self-Disclosure and the Quality of Interpersonal Relationships Among Young Adults in Romantic Relationships in Bandung - Aulia Luthfiyah; Rifqi Farisan Akbar; Prinska Damara Sastri (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
The quality of interpersonal relationships among young adults in romantic relationships is an important aspect of an individual’s psychological and relational life. The quality of these relationships is related to various psychological factors, including avoidant attachment and self-disclosure. This study aims to examine the relationship between avoidant attachment and self-disclosure and the quality of interpersonal relationships among young adults aged 18–25 in Bandung. This study employed a quantitative approach with a correlational design. The sample consisted of 100 young adults currently in romantic relationships and was selected using purposive sampling. Data were collected via a questionnaire and analyzed using the Pearson product-moment correlation test and the coefficient of determination (R²). The results showed that avoidant attachment and self-disclosure together had a strong and significant relationship with the quality of interpersonal relationships (R = 0.743; Adjusted R² = 0.542; p < 0.001). Specifically, avoidant attachment was found to have a significant negative correlation (r = -0.514; p < 0.001), while self-disclosure had a significant positive correlation (r = 0.586; p < 0.001) with the quality of interpersonal relationships. The results of the study indicate that the quality of interpersonal relationships tends to be better among individuals with lower levels of avoidant attachment and higher levels of self-disclosure.